2020
DOI: 10.1097/fjc.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rivaroxaban on Platelet Aggregation

Abstract: Rivaroxaban is a direct oral anti-factor Xa anticoagulant. It has recently been suggested that rivaroxaban may affect platelet function in vitro; however, little is known about the clinical impact of this likely antiplatelet effect and whether this probable phenomenon is dose-dependent. Our aim was to determine whether rivaroxaban at 4 different doses inhibits direct platelet aggregation. We included adult patients of both sexes and who were allocated to one of the following groups depending on the prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…While the Plate-letMapping assay by TEG is not the gold standard for platelet function test, the findings are still compatible with prior studies on DOAC effects on platelets. 17,18 This study was limited due to the low number of participants. It was furthermore limited by few measurement time points: only four time points in phase I and three time points in phase II studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the Plate-letMapping assay by TEG is not the gold standard for platelet function test, the findings are still compatible with prior studies on DOAC effects on platelets. 17,18 This study was limited due to the low number of participants. It was furthermore limited by few measurement time points: only four time points in phase I and three time points in phase II studies.…”
Section: Discussionmentioning
confidence: 99%
“…While the PlateletMapping assay by TEG is not the gold standard for platelet function test, the findings are still compatible with prior studies on DOAC effects on platelets. 17 18…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] However, a study found that even at high doses, rivaroxaban does not directly affect platelet aggregation. [ 11 ] In a recent study, a 72-year-old woman with paroxysmal atrial fibrillation developed a spontaneous spinal epidural hematoma (SSEH) caused by rivaroxaban. The patient’s use of rivaroxaban may be a risk factor for the development of SSEH and a contributor to the patient’s poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Rivaroxaban, an oral direct factor Xa inhibitor, been proven safe and e cacious. In 2020, a study of Hernandez-Juarez et al [27] showed that even a high dose of rivaroxaban did not affect platelet aggregation. This may be the reason that the proportion of platelet hypercoagulation and mixed hypercoagulation increased signi cantly with the extension of postoperative time.…”
Section: Discussionmentioning
confidence: 99%